3D Virtual modelling, 3D printing and extended reality for planning of implant procedure of short-term and long-term mechanical circulatory support devices and heart transplantation - Stepanenko, Alexander; Perez, Laura Maroto; Ferre, Jordi Candela; Ybarra Falcón, Cristina; Pérez de la Sota, Enrique; San Roman, Jose Alberto; Redondo Diéguez, Alfredo; Baladron, Carlos (Frontiers in Cardiovascular Medicine, 2023)
Introduction The use of three-dimensional (3D) reconstruction and printing technology, together with extended reality applied to advanced heart failure adult patients with complex anatomy, is rapidly spreading in clinical practice. We report practical experience with application to acute and chronic heart failure: planning and performing mechanical circulatory device insertion or heart transplantation. Methods From November 2019 until February 2022, 53 3D virtual biomodels were produced for intervention planning (using Virtual/Augmented Reality and/or 3D printing), following a specific segmentation and preprocessing workflow for biomodelling, in patients with advanced heart failure due to structural heart disease or cardiomyopathies. Four of those patients were complex cases requiring mechanical circulatory support implant procedures in our center. Results One short-term and three long-term ventricular assist device system were successfully clinically implanted after application of this technique. In other two cases with extremely high procedural risk, visualized after application of this multimodality imaging, heart transplantation was elected. Conclusion 3D printing based planning and virtual procedure simulation, are of great importance to select appropriate candidates for mechanical circulatory support in case of complex patient anatomy and may help to diminish periprocedural complications. Extended reality represents a perspective tool in planification of complex surgical procedures or ventricular assist device insertion in this setting.